Modeling Hierarchical Aspects of Flexible Manufacturing Systems Using IDEFO and SIMAN/ARENA - Abdulrahman M.A. Al-Ahmari (Journal of King Saud University: Engineering Sciences)
This paper is concerned with description of modeling the hierarchical aspects of a Flexible Manufacturing Cell (FMC) which is a part of a Flexible Manufacturing System (FMS). The modeling techniques IDEFO and SIMAN/ARENA are linked to form a method that can be used to model the hierarchy ol systems such FMC. The static design specifications are modeled using IDEF0 technique, and then the hierarchical model of simulation (the dynamic model) is generated from an IDEF0 model (the static model) using a set of transformation rules and system specifications. This also introduces the possibility of modeling systems hierarchy using SIMAN/ARENA modules. The method developed is illustrated using a typical FMC system.